2011
DOI: 10.1080/00223891.2011.558873
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Gender-Moderated Test Bias on the Levenson Self-Report Psychopathy Scale

Abstract: In this investigation, we examined the validity of Levenson's Self-Report Psychopathy Scale (LSRP; Levenson, Kiehl, & Fitzpatrick, 1995) in a sample of undergraduate students (n = 403). Utilizing a step-down hierarchical multiple regression procedure (e.g., Arbisi, Ben-Porath, & McNulty, 2002), we used LSRP scores to predict psychopathic personality traits to determine the presence of gender-moderated test bias. Results indicate similar correlational magnitudes for men and women. However, systematic over- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
1
13
1
1
Order By: Relevance
“…In general, the associations between psychopathic traits and a variety of externalizing behavior (e.g., aggression, substance abuse, and impulsivity) seem quite similar for men and women (Borroni, Somma, Andershed, Maffei, & Fossati, 2014;de Vogel & Lancel, 2016;Marion & Sellbom, 2011;Phillips, Sellbom, Ben-Porath, & Patrick, 2014;Sellbom et al, 2017;Warren & Burnette, 2013). However, prior studies have also highlighted meaningful gender differences in the associations between psychopathy and specific forms of aggression, with women being more likely to use relational (or social) aggression, and men being more prone to use physical aggression (Colins et al, 2017;Strand & Belfrage, 2005).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In general, the associations between psychopathic traits and a variety of externalizing behavior (e.g., aggression, substance abuse, and impulsivity) seem quite similar for men and women (Borroni, Somma, Andershed, Maffei, & Fossati, 2014;de Vogel & Lancel, 2016;Marion & Sellbom, 2011;Phillips, Sellbom, Ben-Porath, & Patrick, 2014;Sellbom et al, 2017;Warren & Burnette, 2013). However, prior studies have also highlighted meaningful gender differences in the associations between psychopathy and specific forms of aggression, with women being more likely to use relational (or social) aggression, and men being more prone to use physical aggression (Colins et al, 2017;Strand & Belfrage, 2005).…”
mentioning
confidence: 97%
“…However, prior studies have also highlighted meaningful gender differences in the associations between psychopathy and specific forms of aggression, with women being more likely to use relational (or social) aggression, and men being more prone to use physical aggression (Colins et al, 2017;Strand & Belfrage, 2005). Further, a study with nonclinical participants has shown that psychopathy in men exhibits stronger associations with antisocial behavior, aggression, and risk taking behavior, compared to women, who in turn manifest stronger relations between psychopathy and lack of empathy (Marion & Sellbom, 2011). At a facet-level, Miller, Watts, and Jones (2011) found that the antisocial-lifestyle traits of psychopathy were more strongly related to impulsivity among men than women.…”
mentioning
confidence: 97%
“…Gregory and Gretchen). Therefore, the FFM may be a useful model when assessing psychopathy in females, as measures of the FFM may be less gender biased than other psychopathy measures typically used (Forth et al, ; Lilienfeld, ; Marion & Sellbom, ; Skeem & Cooke, ). The vignettes in the current study demonstrated similar ratings; when ratings were different (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These gender-based social norms, therefore, may be impacting the ability to equivalently assess certain psychopathic traits across gender. Furthermore, there may be gender bias in psychopathy measures (Forth et al, 1996;Lilienfeld, 1994;Marion & Sellbom, 2011;Skeem & Cooke, 2010). For example, Marion and Sellbom (2011) found that the Levensen Self-Report Psychopathy Scale may be associated with gender-specific test bias in predicting some components of psychopathy (i.e.…”
mentioning
confidence: 99%
“…Il semble que plusieurs items de l'instrument discriminent peu entre les degrés de psychopathie chez divers groupes de participants (hommes incarcérés, femmes incarcérées, étudiants universitaires ; Sellbom, 2011). En plus, des réserves ont également été émises concernant les différences sexuelles quant à la sévérité des traits présentés, mais également à l'expression de ceux-ci (Marion & Sellbom, 2012). Bref, les questionnements suscités dans la littérature invitent à la réalisation d'études de validation ayant recours à une variété d'échan-tillons provenant de la population générale.…”
Section: Introductionunclassified